Elimination THD using 9- level DC to AC cascade H-bridge multilevel inverter - Mustapha, Mohd Faizal (2013)
Nowaday, electronic devices are very sensitive with harmonics. The needs for a free harmonic and high rating power source is increased to meet the requirement from the industries. This project is to eliminate THD using 9 level cascaded H-bridge of multilevel DC–AC inverter. An Inverter can be broadly classified into single level inverter and multilevel inverter. The result of 9 Cascaded H-Bridge Multilevel Inverter level THD value are compared with 2 level inverter and 5 level Cascaded H-Bridge Multilevel Inverter. The compared multilevel inverter to a single level inverter has advantages like minimum harmonic distortion and higher power output. An implementation of cascaded H-Bridge topology and a sinusoidal pulse with modulation, synthesize a higher quality output power especially with multilevel configuration. Experimental results are included to demonstrate effectiveness of the proposed inverter. This project is to reduce THD contributed by the level of inverter.